Gizli kurucuların şirket kuruluşundaki hukuka aykırılıklardan sorumluluğu - BALKAN, NURDAN (My University, 2022)
Anonim şirketlerde kimlerin kurucu olabileceğine dair TTK m. 337/1 hükmünde düzenlenmiştir. Anonim şirketlerde kurucuların sorumluluk esasları ise TTK m. 549-552 arasında düzenlenmiştir. TTK m. 337/2’de ise kuruluş işlemlerinden hesabına işlem yapılan kişilerin de sorumlu tutulacağı açıkça hüküm altına alınmıştır. Bu çalışmada gizli kurucu olarak adlandırdığımız, TTK m. 337/2 uyarınca sorumlu tutulacak kişilerin sorumluluk esasları incelenecektir.

The regulation on who can be a founder in joint stock companies is regulated in the TTK.art.337/1. The liability principles of the founders in joint stock companies are regulated between TTK.art.549-553. However, it is clearly regulated in the provision of TTK.art.337/2 that the persons who are responsible for the establishment transactions shall also be held responsible. This study examines the principles of responsibility of the persons who shall be held responsible pursuant to TTK.art.337/2, whom are referred to as “secret founders”.
Legal responsibilities of secret founders arising from the establishment of joint stock companies(TTK.m.337/2)
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Ticaret Hukuku; Social Sciences and Humanities; Law; Commercial Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Anonim Şirket; Kuruluş; Kurucu; Gizli Kurucu; Hukuki Sorumluluk; Zarar; Kusur; İbra; Zamanaşımı; Joint Stock Company; Incorporation; Founder (Promoter); Secret Founder; Legal Liability; Loss; Fault; Acquittance; Limitation